Can a Naturally Occurring Pathogen Threat Change Social Attitudes? Evaluations of Gay Men and Lesbians During the 2014 Ebola Epidemic. (July 2016) - Inbar, Yoel; Westgate, Erin C.; Pizarro, David A.; Nosek, Brian A.
Previous evidence linking disease threat and social attitudes suggests that a highly salient society-wide pathogen threat should lead to more negative attitudes toward gay men and lesbians. Using a sample of 248, 922 Americans recruited via the Project Implicit website, we tested whether implicit attitudes toward gay men and lesbians shifted as a result of the 2014 Ebola virus outbreak. Regression discontinuity analyses, but not t -tests, showed evidence of a small shift in implicit (but not explicit) attitudes at the height of public concern over Ebola. These results could be interpreted as providing partial support for the effects of naturally occurring pathogen threats on social attitudes. Alternatively, given the large size of our sample, the mixed evidence and small effects may reflect a boundary condition for the operation of the behavioral immune system.